ANALYSIS OF RACIAL DISCRIMINATION ASPECTS BASED ON GORDON ALLPORT’S THEORY DEPICTED IN FRUITVALE STATION MOVIE (2013) - atmantika, Zanuwar; Ahsani, Nizam; Ahdiani, Ulaya; Kasiyarno,; Latifah Ananda, (Elite : English and Literature Journal, 2022)
Fruitvale Station is a movie based on the true story of a shooting at a Fruitvale Station in Oakland, California, by a white police officer named Johannes Mehserle against a black man named Oscar Grant III. Oscar Grant, who was the victim of a conflict on a train that stopped at Fruitvale Station, was instead made a suspect in the incident by police officers who wanted to secure the train and was shot dead without any evidence of guilt or legal proceedings first. Thus, using Gordon Allport's Intentional, Explicit Discrimination theory, the authors analyzed the types of racial discrimination in the movie Fruitvale Station. Racial discrimination includes verbal antagonism, avoidance, segregation, physical attacks, and extermination. The author’s method to collect data is qualitative descriptive by examining the Fruitvale Station movie to understand the movie as the primary data. The authors will also include the dialogue from the script as secondary data. The findings of this study reveal five discriminatory behaviors (particularly discrimination based on race) committed by white characters against African-American characters in this movie.